2010
DOI: 10.1128/aem.02807-09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endochitinase-Transformed White Spruce on Soil Fungal Biomass and Ectendomycorrhizal Symbiosis

Abstract: The impact of transgenic white spruce [Picea glauca (Moench) Voss] containing the endochitinase gene (ech42) on soil fungal biomass and on the ectendomycorrhizal fungi Wilcoxina spp. was tested using a greenhouse trial. The measured level of endochitinase in roots of transgenic white spruce was up to 10 times higher than that in roots of nontransformed white spruce. The level of endochitinase in root exudates of three of four ech42-transformed lines was significantly greater than that in controls. Analysis soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…Hampp et al (1996) found that transformation of poplars with hygromycin marker or indoleacetic acid biosynthetic genes did not affect the ability of Amanita muscaria to form mycorrhizae. Results similar to these examples were obtained in work with endochitinase-transformed white spruce; Stefani et al (2010) did not detect any interference with ectendomycorrhizal Wilcoxina spp. and Lamarche et al (2011) did not detect any significant impacts of transformation on fungal biomass or community structure in such trees.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hampp et al (1996) found that transformation of poplars with hygromycin marker or indoleacetic acid biosynthetic genes did not affect the ability of Amanita muscaria to form mycorrhizae. Results similar to these examples were obtained in work with endochitinase-transformed white spruce; Stefani et al (2010) did not detect any interference with ectendomycorrhizal Wilcoxina spp. and Lamarche et al (2011) did not detect any significant impacts of transformation on fungal biomass or community structure in such trees.…”
Section: Discussionsupporting
confidence: 84%
“…Laboratory, greenhouse, and field studies have largely reported little to no impact of transformation on microbial communities of soils (Hampp et al, 1996; Kaldorf et al, 2002; Pasonen et al, 2005; Lamarche and Hamelin, 2007; Newhouse et al, 2007; Seppänen et al, 2007; Oliver et al, 2008; Stefani et al, 2009, 2010; Lottman et al, 2010; Lamarche et al, 2011), although some have found significant changes in particular microbial groups (LeBlanc et al, 2007; Andreote et al, 2009). These responses to genetic modifications occur within a wider context of variable natural genotypic influences on microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Vauramo et al (2006) showed no negative effect on fungal biomass associated with decaying leaf litter by contrasting the ergosterol content of litters made of control and chitinase-expressing silver birch leaves after 8 months of decomposition in the field. Stefani et al (2010) showed that an increase of up to 10 times in endochitinase levels within root tissues of transformed white spruce lines did not prevent the colonization and development of ectendomycorrhizal symbiosis by Wilcoxina sp. They did not find evidence of a difference in the fungal structure community associated with transgenic and wild-type genotypes clearly related to the expression of sugar beet chitinase IV.…”
Section: Discussionmentioning
confidence: 98%
“…This growth reduction appeared to be associated with high lignin content and overexpression of peroxidase and glucanase activity (Faize et al, 2003), which are both involved in plant disease response to fungal pathogens. However, Stefani et al (2010) showed that ech42-transformed white spruce released endochitinase into soil through root exudates and the level of endochitinase in roots of transgenic white spruce was up to 10 times higher than that in roots of untransformed white spruce. These metabolism modifications could, in turn, have unexpected effects on nontarget fungal communities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation